Primary scrotal diffuse large B-cell lymphoma with skip metastasis to the mediastinum: a case report and literature review - Wang, Ziye; Tang, Wen; Xiao, Daihui; Li, Yi; Liang, Guobiao; Zhao, Zeju; Wu, Tao (Frontiers in Oncology, 2025)
Primary scrotal diffuse large B-cell lymphoma (PS-DLBCL) is an uncommon disease. Due to the scarcity of case reports, its atypical clinical manifestations often lead to misdiagnosis. An 81-year-old male patient presented with a rapidly enlarging, painless left scrotal mass. Imaging studies suggested sarcoma or seminoma. A chest computed tomography (CT) scan incidentally revealed mediastinal masses. Laboratory tests showed significantly elevated lactate dehydrogenase and β2-microglobulin levels. Postoperative histopathological examination confirmed DLBCL with a germinal center B-cell subtype, accompanied by an abnormally high Ki-67 proliferation index (>90%) and P53 translocation. FISH testing ruled out double-hit lymphoma. Notably, staging evaluation identified “isolated mediastinal involvement” without inguinal, pelvic, or retroperitoneal lymph node involvement, defining a “skip metastasis” pattern. The patient was diagnosed with stage IV disease and a high-risk International Prognostic Index (IPI) score of 5. Refusing chemotherapy, the patient died within 3 months of initial diagnosis due to rapid disease progression. This case highlights that scrotal lymphoma is rare yet highly aggressive, with clinical presentations frequently confused with common malignancies. Diagnosis relies on biopsy and immunohistochemistry, requiring clinicians to remain vigilant for early detection and intervention.